Severe palmoplantar keratoderma: a cutaneous complication from sub-optimally controlled type 2 diabetes - Fatima Iqbal; Kevin Phan; Wah N Cheung (Endocrinology, Diabetes & Metabolism Case Reports)
Palmoplantar keratoderma (PPK), characterised by excessive epidermal thickening of the skin on the palms and/or plantar surfaces of the feet, can be hereditary or acquired. Here, we report a case of a 53-year-old woman with a history of sub-optimally controlled diabetes mellitus presenting with fevers and decreased Glasgow Coma Scale (GCS) to a tertiary hospital. She was diagnosed with diabetic ketoacidosis (DKA), with blood glucose at 40 mmol/L and ketones at 7 mmol/L, in the setting of a methicillin-sensitive Staphylococcus aureus necrotising soft tissue back infection. Her medical history included diabetes managed with insulin but no engagement with an endocrinologist or allied health support. Examination revealed an infected, necrotic back wound on her left mid-upper back that required surgical debridement and broad-spectrum IV antibiotics. In addition, she exhibited marked plantar keratoderma and onychogryphosis, reportedly present and worsening over approximately two years. She was prescribed 40% urea cream twice daily, resulting in gradual sloughing of the hyperkeratotic skin within a few weeks. Her HbA1c was 10.4%, and she tested negative for diabetes antibodies, indicating type 2 diabetes. Treatment included an insulin–dextrose infusion until DKA resolved, followed by twice daily insulin degludec/aspart (Ryzodeg 70/30) and metformin. The PPK was attributed likely secondary to sub-optimally managed diabetes.